2017
DOI: 10.4081/aiua.2017.2.120
|View full text |Cite
|
Sign up to set email alerts
|

Psychologic and sexual dysfunction in primary and secondary infertile male patients

Abstract: Objective: The aim of this study was to compare depression and sexual dysfunctions observed in primary and secondary infertile patients. Material and method: The study was performed in 39 primary and 31 secondary infertile male patients. Male sexual health was evaluated using the International Index of Erectile Function (IIEF) score and depression with Beck Depression Inventory (BDI). Results: Mean age of the participants and their partners were 31.54 ± 5.37 (range, 24-48 yrs), and 28.16 ± 5.58 (range, 20-46 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 21 publications
2
20
1
Order By: Relevance
“…In a study comparing the depression status of primary and secondary infertile men, it was reported that depression was more common in secondary infertile patients, which was suggested to be due to anxiety related to losing the ability to have children after having successful pregnancies. 2 In contrast to this study, in our study we found that SSAS, HAI, BAI, and BDI scores were higher in the primary infertile patients compared to the secondary infertile patients. In traditional societ-ies, such as Turkey, great importance is given to reproduction and the continuity of the family, and couples are under pressure from their families and the community.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In a study comparing the depression status of primary and secondary infertile men, it was reported that depression was more common in secondary infertile patients, which was suggested to be due to anxiety related to losing the ability to have children after having successful pregnancies. 2 In contrast to this study, in our study we found that SSAS, HAI, BAI, and BDI scores were higher in the primary infertile patients compared to the secondary infertile patients. In traditional societ-ies, such as Turkey, great importance is given to reproduction and the continuity of the family, and couples are under pressure from their families and the community.…”
Section: Discussioncontrasting
confidence: 99%
“…23 There are many studies evaluating psychological well-being of patients with infertility, especially their anxiety and depression levels. 2,[4][5][6][7][8][9][10][11][12]24 Increased stress-related anxiety and depression have been shown to reduce the success of in vitro fertilization by affecting cytokine levels. 11 In addition, it has been emphasized that semen parameters were adversely affected as a result of changes in the blood hormonal levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16 Another study by Aytac Sahin et al the frequency of the depression and erectile dysfunction seen in the patients with secondary infertility was seen significantly higher than the patients with primary infertility. 17 This study showed infertile couple with stress had at least education up to high school. Wischmann T et al in their study showed high educational profile had specific higher prevalence of idiopathic infertility.…”
Section: Discussionmentioning
confidence: 75%